2019
DOI: 10.1002/wnan.1608
|View full text |Cite
|
Sign up to set email alerts
|

Biocorona‐induced modifications in engineered nanomaterial–cellular interactions impacting biomedical applications

Abstract: When nanoparticles (NPs) enter a physiological environment, a complex coating of biomolecules is absorbed onto their surface, known as the biocorona (BC). This coating alters nanomaterial physical properties, modulating cellular viability, internalization, and immune responses. To safely utilize NPs within medical settings, it is necessary to understand the influence of the BC on cellular responses. Due to the variety of cell types, NPs, and physiological environments, responses are variable; though trends do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 127 publications
(144 reference statements)
0
7
0
Order By: Relevance
“…These proteins adsorb on the surface of NPs to form a structure known as a protein "corona." [1][2][3][4][5][6][7][8][9][10][11][12][13] However, the in vivo milieu consists of many different types of biomolecules, not just proteins. For example, recent work has examined the formation of lipid and metabolite coronas on NPs.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins adsorb on the surface of NPs to form a structure known as a protein "corona." [1][2][3][4][5][6][7][8][9][10][11][12][13] However, the in vivo milieu consists of many different types of biomolecules, not just proteins. For example, recent work has examined the formation of lipid and metabolite coronas on NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much research has been done in escaping the immune system upon in vivo conditions by exploiting the protein corona, using a preformed protein corona or biomimetic protein corona on NPs [15,94]. For instance, coating of NPs with endogenous peptides such as CD-47 (an integrin-associated protein) was shown to increase the circulation time of NPs by avoiding macrophage uptake [95].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin (considered a dysopsonin) may be beneficial on the surface of CtNPs. Indeed, it was found a high interaction between albumin coated NPs and endothelial cells, in turn prolonging their circulation time [94]. Conversely, Nguyen et al [98] found that precoating of gelatin-oleic NPs with albumin increased the cellular uptake of a human embryonic kidney cell line (HEK 293) while decreasing that one of a human adenocarcinoma alveolar basal epithelial cells (A549).…”
Section: Discussionmentioning
confidence: 99%
“…8,[20][21][22][23][24][25][26] The specific proteins that adsorb on the NP surface determine the subsequent interactions of the NP with cells and organs including cellular internalization, immune response, biodistribution, and circulation time. 22,24,25,[27][28][29] The majority of research on the protein corona, including our own, [30][31][32] has focused on blood serum proteins relevant to nanomedicines. In comparison, inhalation of NPs brings the NPs into contact with the more complex environment of lung lining fluid.…”
Section: Introductionmentioning
confidence: 99%